Current Issues of "Laundering of Dirty Money" and the Fight Against Corruption - Musayev, H.M. (Herald of Azerbaijan Engineering Academy, 2024)
The article examines the world experience of combating "money laundering" and corruption in individual countries in modern times, and also examines the existing legislative framework in the relevant field. In particular, extensive information was given about the measures implemented in the fight against "money laundering" and corruption, and information was given about the work done in this field in our country. Research methods such as systematic analysis, analogy, retrospective analysis and scientific generalization were used in the article.